1997
DOI: 10.1002/elan.1140091703
|View full text |Cite
|
Sign up to set email alerts
|

Microelectrode procedures for the determination of silicate and phosphate in waters – fundamental studies

Abstract: The voltammetry of the molybdosilicate and molybdophosphate complexes, formed by the addition of hexafluorosilicate and phosphate to an acidic sodium molybdate solution, have been defined at gold microdisk electrodes. It is shown that the reaction conditions influence both the kinetics of formation of the complexes and their voltammetry. It is possihle to find conditions where the steady state amperometric response of the Au microdisk electrodes allows a rapid and convenient method for the determination of sil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
29
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 25 publications
5
29
1
Order By: Relevance
“…A previous article [14] has reported on the voltammetry of the molybdosilicate and molybdophosphate complexes, formed by the reaction of hexafluorosilicate and orthophosphate, respectively, with molybdate in an acidic solution (pH 1-2). It was shown that in aqueous solutions, pH 1-2, both complexes show two reduction waves in the potential range þ400 mV to þ100 mV (vs. SCE).…”
Section: Introductionmentioning
confidence: 99%
“…A previous article [14] has reported on the voltammetry of the molybdosilicate and molybdophosphate complexes, formed by the reaction of hexafluorosilicate and orthophosphate, respectively, with molybdate in an acidic solution (pH 1-2). It was shown that in aqueous solutions, pH 1-2, both complexes show two reduction waves in the potential range þ400 mV to þ100 mV (vs. SCE).…”
Section: Introductionmentioning
confidence: 99%
“…Ascorbic acid and tin (II) chloride are some of the reducing agents used for spectrophotometric detection. As a routine analytical method, the procedure is carried out in A c c e p t e d M a n u s c r i p t 4 an automated continuous flow assembly [18]. Spectrophotometric analyses often involve selective extraction into an organic solvent or addition of organic molecules such as tartrate, oxalate, mannitol, acetone or butanone.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the effect of their addition could vary, depending upon the order in which they are added. Furthermore this method suffers from interference arising from arsenates, silicates and other anions [18]. Thus none of these methods is entirely and universally satisfactory.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Conventional voltammetric determinations have also been reported, in which phosphate ion is determined as heteropoly acid or a molybdophosphate complex. [18][19][20] A simple flow-injection system utilizing a thin-layer amperometric detector for phosphate ion has also been reported. 21 A voltammetric sensor used to detect phosphate ion at a liquid|liquid interface has been reported.…”
Section: Introductionmentioning
confidence: 99%